Investigation of the impact of heat treatment on the layer formation of AlSi-coated boron-manganese steel - He, Franz; Merklein, Marion (INTERNATIONAL DEEP-DRAWING RESEARCH GROUP CONFERENCE (IDDRG 2021), 2021)
Hot stamping is a well-established technology for producing safety relevant car components. The usage of hot stamping allows for reduced sheet thicknesses and weight of formed parts due to an increase in strength because of martensitic phase transformations. To prevent surface carburization and the formation of oxide layers AlSi coatings are applied to the workpiece surface. Due to a lack of suitable lubricants at process temperatures of over 800 °C, severe friction and wear affect the final part quality. Furthermore, process temperatures influence the layer formation and surface roughness due to diffusion processes. Consequently, a deeper process understanding is needed to acquire detailed knowledge of the impact on the tribological behavior to increase part quality and reduce tool wear. To this end the influence of heat treatment parameters on the coating layer and the subsequent layer formation is analyzed by comparing the resulting material composition and surface roughness. This is achieved by analyzing the impact of the furnace temperature and holding time on an AS150 coating and determining the effect of the parameters via metallographic investigation and tactile measuremen
CRIS-Team WoS Importer:2021-11-05